Knowledge management practices in academic library : a case study of Dar Al-Hikmah Library (IIUM) - Marahani binti Suni (Kuliyyah of Information and Communication Technology, International Islamic University Malaysia, 2016)
Knowledge sharing is a crucial culture for a successful knowledge management implementation in an organization like the academic library. Knowledge management practices cannot be effectively implemented if the members of the organization did not want to share and did not have sharing culture. It is also significant for the library Top management to know how the librarians perceive knowledge management and what are the issues faced by the librarians to acquire and share knowledge within the work place in order to cultivate a successful knowledge management practices in the library. This study investigates the perceptions of IIUM librarians on knowledge sharing, current methods used to share and disseminate knowledge, issues in acquiring and sharing knowledge within the library, and the library Top management efforts to inculcate knowledge management practices in the library. Case study methodology is employed in a combination of qualitative and quantitative data consist of questionnaire and interview involving the librarians of Dar Al-Hikmah Library (IIUM). The results revealed that knowledge sharing practices existed in this library. Nevertheless, there are some issues identified as the obstacles in acquiring and sharing knowledge which are caused particularly by the librarians and the library Top management. The conclusion of this study is that both the librarians and the library Top management have a critical role to preserve and disseminate valuable knowledge in the organization.